Cotidiano, cultura popular e identidade na TV comunitária Canal Capibaribe-PE. - Nascimento Júnior, Waldelio Pinheiro do (2015)
The impact of modernity changed social relations and interfered in the formation and preservation of traditional communities; especially by changes arising from commercial and cultural processes of globalization. Such processes found in culture, education and hegemonic media, media for dissemination and maintenance of ideologies which, for the most part do not have affirmative spaces for diversity, for minorities and their social struggles. Against this backdrop, the very ethnic and traditional communities have produced, through elements of popular culture and traditions, forms of resistance to global influences and media messages. Among these forms are the community media, affirmative spaces dedicated to independence, role and otherness. One example was the creation in 2001 of the first community cable television station in the northeastern of Brazil – the Capibaribe Channel, in Recife, which aims to open space in the media to communities at risk, ethnic minorities and social. Include in the agenda of the channel, alternative culture groups, popular and folk, as well as manifestations of African origin. The Channel also conducts workshops of critical training and civic education, and training in audiovisual production with individuals of communities - from which emerge materials and documentaries that portray the difficulties and the positive aspects of their daily lives. The participants of these actions, and have valued their culture, identify with social struggles and spaces, which contributes to increased self-esteem and the reaffirmation of identities. This study analyzes the role of community media in the production and reinvigoration of communion and solidarity ties, vital to the development of community ideals. The qualitative survey, whose base is an observational study, using exploratory method, with dialectical approach supported by Cultural Studies and the Folkcommunication Studies. The observation proposed here scrutinizes the relationship between Capibaribe Channel and the community, seeing how the community television station is done recording and broadcasting of popular culture space, while the second appropriates media and production technique to be new expression of spaces and serving everyday, reaffirming and strengthening cultural identities.